The Influence of Product Quality and Price on Samsung Smartphone Purchasing Decisions among Students of Universitas Negeri Padang - Ramadhani, Delfi; Hayati, Annur Fitri; Rahmidani, Rose (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
The aim of this study is to investigate the impact of product quality (X1) and price (X2) on Samsung smartphone purchasing decisions (Y) among students at Universitas Negeri Padang. The research approach employed was exploratory research, with variables measured on a Likert scale. The data collection method is a questionnaire using Google Form, with the research population consisting of all active students at Universitas Negeri Padang. The sampling technique is purposive sampling with a sample size of 97. The sample criteria included active students at Universitas Negeri Padang (UNP) at the time of the study who had acquired a Samsung smartphone. The data is processed using SPSS software version 20, which includes descriptive analysis, classical assumption analysis, and hypothesis testing. The study found that product quality and price have a significant and favorable impact on purchasing decisions.